Pendidikan Kesehatan Reproduksi Dan Seksualitas Pada Remaja SMPLB Hambatan Intelektual Untuk Mencegah Terjadinya Kekerasan Seksual Di Kabupaten Jombang - Kolifah; Nur Laila Faizah; Aliza, Ana Dyah (Journal of Health Innovation and Community Services, 2023)
Reproductive health is health that focuses on mental, physical and social well-being that relates to everything about the reproductive system, activities and functions. The educational process is carried out to direct the child so that he will have provisions in his life later. One of them is children with special needs who are low intellectual generally experience obstacles in carrying out activities. These limitations are often misused so that sexual violence also occurs to them. The purpose of this service is to prevent sexual violence in Jombang Regency. This activity method is composed of preparation, planning, implementation and evaluation. The activities carried out are the provision of material to teachers and guardians of students using teaching aids. It is proven that the suitability of the activity is based on the increased enthusiasm and understanding of teachers and student guardians regarding reproductive health. The hope is that in the future there will be further progress regarding reproductive health education so that there will be less cases of sexual harassment in Jombang Regency, especially children with special needs.